2008
DOI: 10.1103/physrevb.78.014107
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced shear bands in an energetic molecular crystal: Application of shock-front absorbing boundary conditions to molecular dynamics simulations

Abstract: W91INF-05-1-0265 REPORT NUMBER REPORT ~'u~mER 48101-EG-MUR The views, opinions andlor findings contained in this report are those of the author(s) and should not be construed as an official Department of the Army position, policy or decision, unless so designated by other documentation. Approved for public release; federal purpose rights The response of the energetic molecular crystal cyclotrimethylene trinitramine (RDX) to the propagation of planar shock waves nonnal to (100) has been studied using large-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 40 publications
5
123
0
Order By: Relevance
“…The initial temperature was T = 300 K. Molecules on the surface of the void prior to shock arrival are colored red. The observation of the nucleation and growth of nanoscale shear bands in the material to the left of the void, and symmetric collapse of the void with small jets meeting near the stagnation plane at angles approximately ±45° relative to the direction of shock propagation (blue incursions into the red region in the right-hand panel), are both consistent with expectations 13,22 based on previous simulation results for this shock orientation and impact strength. In the coming year we will perform detailed studies of void collapse for multiple impact speeds, void configurations, and crystal diameters.…”
Section: Molecular Dynamics Simulations Of Void Collapse In (100)-orisupporting
confidence: 78%
“…The initial temperature was T = 300 K. Molecules on the surface of the void prior to shock arrival are colored red. The observation of the nucleation and growth of nanoscale shear bands in the material to the left of the void, and symmetric collapse of the void with small jets meeting near the stagnation plane at angles approximately ±45° relative to the direction of shock propagation (blue incursions into the red region in the right-hand panel), are both consistent with expectations 13,22 based on previous simulation results for this shock orientation and impact strength. In the coming year we will perform detailed studies of void collapse for multiple impact speeds, void configurations, and crystal diameters.…”
Section: Molecular Dynamics Simulations Of Void Collapse In (100)-orisupporting
confidence: 78%
“…We attempted to reproduce structural features of RDX behind the shock front, as captured in an earlier MD study 18 [and shown in Fig. 4(a)].…”
Section: Figurementioning
confidence: 99%
“…These hotspots in energetic materials form through mechanisms such as compression of voids, friction between crack surfaces inside the material, and localized shear deformation. [1][2][3][4][5] Heating due to each of these mechanisms depends on the histories of the states of local stress and rate of deformation in the material. Existing literature examines the behavior of energetic crystals and polymer-bonded explosives (PBXs) in two general forms: as single crystals with anisotropic material properties, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and as heterogeneous collections of energetic grains with isotropic material properties.…”
Section: Introductionmentioning
confidence: 99%
“…
We investigate the response of polycrystalline HMX 3,5,3,5, under impact loading through a 3-dimensional mesoscale model that explicitly accounts for anisotropic elasticity, crystalline plasticity, and heat conduction. This model is used to quantify the variability in temperature and stress fields due to random distributions of the orientations of crystalline grains in HMX under the loading scenarios considered.
…”
mentioning
confidence: 99%